G270(P) Prevalence of Coeliac Disease in Children with Down Syndrome in Ireland. (24th May 2017) - Alsaffar, M; Balfe, J; McGrane, F; Nadeem, M; Quinn, S; McDonald, D; Coughlan, D; Curtis, E; Molloy, E
Abstract : Aim: Down syndrome (DS) is one of the commonest chromosomal abnormalities with an incidence of 1:444 births and the highest prevalence of DS in Europe being in Ireland. Individuals with DS are at increased risk of developing coeliac disease (CD) compared with the general population (5%–10% vs. 1%). The European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) and the National Institute for Health and Care Excellence (NICE) recommend that individuals with DS are screened for CD. We aimed to determine the rate of screening for, and the prevalence of CD in a cohort of children with DS attending a Paediatric Hospital in Ireland. Methods: Children with DS attending the hospital were identified from records held by the Research Nurse for Children with DS. Blood results were obtained from the hospital laboratory system and online letters portal. Charts were pulled if information was unavailable from the above routes. Information was collated on Microsoft Excel. Ethics approval was obtained from the hospital ethics committee. Results: A total of 265 children with DS attend the paediatric service in our hospital. 213 (80%) of the children with DS were screened for CD using immunoglobulin A anti-tissue transglutaminase antibody (IgA-tTG) values. 171 of these 213 children (80%) also had serum immunoglobulin A (IgA) measured. 20/213 (9.4%) had IgA-tTG levels above the reference range and antiendomysial antibody (EMA) levels were subsequently measured in these 20 children and were positive in all cases. 14/213 children with DS were confirmed to have CD at a rate of 6.6%. CD was confirmed in 13 children using oesophagogastroduodenoscopy (OGD) and duodenal biopsy. One patient was diagnosed on the basis of clinical and biochemical findings alone. Three further children await gastroenterology assessment for positive screening results. IgA-tTG and EMA results returned to normal in two further cases. One child had a normal biopsy despite high IgA-tTG and EMA levels. Conclusion: The rate of CD in children with DS in our cohort is higher than that of the general population and supports routine screening for IgA-tTG in patients with DS.